2005
DOI: 10.1007/s00432-005-0059-3
|View full text |Cite
|
Sign up to set email alerts
|

Observation of circulating tumour cells in patients with non-small cell lung cancer by real-time fluorescent quantitative reverse transcriptase-polymerase chain reaction in peroperative period

Abstract: A considerable proportion of patients who appear to have resectable NSCLC might be regarded as having systemic disease, which is often undetectable by current tumour staging method. In terms of a marker used for the NSCLC patients who undergo operation, CEA is more suitable than CK19. The CK19-expressing epithelial cells are released intraoperatively into the circulation, meanwhile CEA-expressing tumour cells are disseminated mostly postoperatively. Surgical manipulation could promote the release of tumour cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 17 publications
0
38
2
Order By: Relevance
“…An increase in CTC during and/or after surgery has also been observed in studies that assessed peripheral blood samples using different detection methods (18)(19)(20)(21). Interestingly, CK19 and CEA transcripts have shown a different peri-operative kinetic when used as markers of CTC dissemination (20). The value of CK19 mRNA during the operation was significantly higher than that of pre-operation and postoperation; in contrast, the post-operative levels of CEA mRNA were significantly higher than those of preoperation and those of operative day.…”
Section: Detection and Prognostic Value Of Ctc In Early Nsclcmentioning
confidence: 61%
See 2 more Smart Citations
“…An increase in CTC during and/or after surgery has also been observed in studies that assessed peripheral blood samples using different detection methods (18)(19)(20)(21). Interestingly, CK19 and CEA transcripts have shown a different peri-operative kinetic when used as markers of CTC dissemination (20). The value of CK19 mRNA during the operation was significantly higher than that of pre-operation and postoperation; in contrast, the post-operative levels of CEA mRNA were significantly higher than those of preoperation and those of operative day.…”
Section: Detection and Prognostic Value Of Ctc In Early Nsclcmentioning
confidence: 61%
“…In this respect, Hashimoto and collaborators (15) found that the median number of CTC in PV samples increased from 4 to 60 in 30 consecutive primary lung cancer patients who underwent lobectomy through open thoracotomy. An increase in CTC during and/or after surgery has also been observed in studies that assessed peripheral blood samples using different detection methods (18)(19)(20)(21). Interestingly, CK19 and CEA transcripts have shown a different peri-operative kinetic when used as markers of CTC dissemination (20).…”
Section: Detection and Prognostic Value Of Ctc In Early Nsclcmentioning
confidence: 72%
See 1 more Smart Citation
“…Several studies [16][17][18][19][20][21][22][23][24][25] , published in this area with a focus on lung cancer, have provided knowledge of the clinical significance of tumor markers for the detection of MRD. Of these the most specific marker appears to be Lunx protein 16,17,25 , although some other markers appear to be applicable for MRD detection in lung cancer, especially CEA (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Cells expressing CK19 were already circulating during the operation, and cells that expressed CEA were frequently disseminated only in the postoperative period. Surgical manipulation may lead to the dissemination of tumor cells into the blood circulation but this could be prevented by ligation of the pulmonary vein before pulmonary artery ligation 24 . In 2002, Masato et al focused on small-cell lung cancer (SCLC), which tends to hematogeníc rapid progression.…”
Section: Detection Of Minimal Residual Disease In Lung Cancermentioning
confidence: 99%